Odpowiedzi

2009-10-22T18:57:33+02:00

4⁻¹-3(⅔)⁻²
___________=
5-(½)⁻¹
(¼-3x⁹/₄):5-2=(¼-²⁷/₄):3=(-²⁶/₄):3=²⁶/₄x¹/₃=²⁶/₁₂=¹³/₆=2⅙
Najlepsza Odpowiedź!
2009-10-22T19:01:04+02:00
¼- 3 × ³/₂ × ³/₂= ¼ - 3 × ⁹/₄ = ¼ - ²⁷/₄ = -²⁶/₄ = ²⁶/₄ ÷ 3 =
____________ __________ ________ ____
5-2 3 3 3

= ²⁶/₄ × ⅓ = ²⁶/₁₂ = 2 ²/₁₂ = 2 ¹/₆

soryy nie czytelnie mi wyszło , trójki mają być wszędzie w mianowniku ..
2009-10-22T19:08:37+02:00
4⁻¹-3(⅔)⁻²
___________=
5-(½)⁻¹

¼-(¹¹/₃)⁻²
__________=
5-2

¹¹/₄₄-¹²/₄₄
_________=
3

-¹/₄₄ *¹/₃= -¹/₁₃₂